Ottolenghi test kitchen : extra good things : bold, vegetable-forward recipes plus homemade sauces, condiments, and more to build a flavor-packed pantry - Murad, Noor; Ottolenghi, Yotam (Clarkson Potter/Publishers, 2022)
"The superteam of chefs behind the New York Times bestseller Shelf Love delivers maximum-flavor recipes with make-ahead condiments, sauces, and more toppings that transform any dish into an Ottolenghi favorite Extra Good Things is all about the secret culinary weapons--condiments, sauces, dressings, and more make-ahead items--that can make a good meal spectacular. The abundant, vegetable-forward recipes in this collection give you a delicious, hearty dish, plus that special takeaway--a sauce, a sprinkle, a pickle!--that you can repurpose time and time again in other recipes throughout the week, with limitless opportunity. These extras help you stock your fridges and pantries the Ottolenghi way, so you can effortlessly accessorize plates with pops of texture and color, acidity and heat, and all the magical flavor bombs that keep you coming back for more. And this is where the fun really begins, with extras like feta marinated with spices and herbs, featured in a dish of oven-braised chickpeas that's used again for a flavorful salad or swirled into soup. Za'atar-spiked burst tomatoes top a polenta pizza for dinner, then reappear on the best-ever bruschetta or as the easiest weeknight sauce for pasta. Or a crispy, crunchy panko topping full of ginger, shallots, and sesame that you first meet on soba noodles but you'll want to put on...well, just about everything. Whether it's a tart, sassy punch of pickled chile or an herbaceous salsa to lighten and brighten, Extra Good Things shows you how to fill your kitchen with adaptable, homemade ingredients that will make any dish undeniably "Ottolenghi.""--